Adherence barriers and interventions to improve ART adherence in Sub-Saharan African countries: A systematic review protocol - Buh, Amos; Deonandan, Raywat; Gomes, James; Krentel, Alison; Oladimeji, Olanrewaju; Yaya, Sanni (Université d'Ottawa | University of Ottawa, 2022)
The HIV/AIDS pandemic continues to be a major public health concern, particularly in Sub-Saharan Africa (SSA). Despite efforts to reduce new infections and deaths with the use of antiretroviral therapy (ART), SSA countries continue to bear the heaviest burden of HIV/AIDS globally, accounting for two-thirds of global new infections. The goal of this review is to identify common barriers to ART adherence as well as common effective interventions that can be implemented across SSA countries to improve ART adherence.
Keywords: Adult; Africa South of the Sahara; Cross-Sectional Studies; Humans; Meta-Analysis as Topic; Patient Compliance; Retrospective Studies; Review Literature as Topic; Systematic Reviews as Topic; HIV Infections